Bimetallic site zinc-based porphyrin organic framework positive electrode material, and preparation method and application thereof

CN122940969APending Publication Date: 2026-10-20ANYANG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610908435.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]针对现有水系锌碘电池中碘正极存在的多碘化物穿梭扩散、氧化还原反应动力学迟缓、界面转化能垒高、活性物质易流失、电池循环稳定性差以及传统有机框架宿主锚定能力弱、缺乏本征催化活性等核心技术问题,本发明提供一种双金属位点锌基卟啉有机框架正极材料及其制备方法

Benefits of technology

[0017]A、本发明正极材料制备工艺简单、条件温和、普适性强,可拓展制备多种卤化锌改性有机框架正极材料,为高性能、长寿命、大规模储能型水系锌碘电池正极材料的结构设计与可控制备提供了全新的设计思路与技术支撑,具备极高的工程应用价值与产业化前景。通过分步缩合聚合与后合成精准配位改性策略,成功构筑了双活性位点协同的卟啉基有机框架正极材料,有效解决了传统锌碘电池碘正极多碘穿梭严重、氧化还原动力学迟缓、活性物质易流失、电极界面稳定性差及循环寿命短等技术弊端。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a bimetallic site zinc-based porphyrin organic framework cathode material, its preparation method, and its applications, belonging to the field of inorganic materials. 5,5'-dialdehyde-2,2'-bipyridine (Bpy) and pyrrole are reacted under reflux and stirring in propionic acid solvent. The system is cooled, and the solid product is collected by centrifugation, then washed successively with deionized water and ethanol. The solid is vacuum dried to obtain a black powder POF-Bpy, which is then uniformly dispersed with anhydrous zinc iodide in DMF and reacted under heating and stirring. The product ZnI-POF-Bpy is collected by cooling and filtration. This material exhibits a monodisperse, near-spherical morphology with highly uniform particle size and an average diameter of approximately 1 μm. The particle surface displays a typical rough porous structure, assembled from a large number of nanoparticles. The bimetallic site zinc-based porphyrin organic framework cathode material of this invention exhibits excellent electrochemical performance, providing a practical new approach for the development of high-stability zinc-iodine batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a bimetallic site zinc-based porphyrin organic framework cathode material and its preparation method, which is applied to the cathode of a high-stability zinc-iodine battery and belongs to the field of new energy materials. Background Technology

[0002] Addressing the urgent need for large-scale energy storage in the construction of carbon neutrality and new power systems, aqueous zinc-iodine batteries are considered promising next-generation energy storage devices due to their intrinsic safety, low cost, high ionic conductivity, environmental friendliness, and the considerable theoretical capacity of iodine-based cathodes. Iodine-based cathodes can achieve... (Two electrons) A multi-stage reversible redox reaction (with four electrons), combined with a stable voltage platform and abundant zinc anode, can achieve considerable energy density. However, the practical application of aqueous zinc-iodine batteries has long been constrained by two intrinsic problems: one is the formation of soluble polyiodides during charging and discharging. First, iodine species are highly prone to diffusion and migration, causing severe shuttle effects, resulting in irreversible loss of active materials, zinc anode corrosion, and self-discharge. Second, iodine species have poor intrinsic conductivity and high interfacial conversion energy barriers, while traditional carbon-based hosts can only provide weak physical confinement and lack intrinsic catalytic sites, making it difficult to achieve efficient iodine adsorption and rapid conversion synergy, which severely limits the battery's capacity utilization, rate performance, and cycle stability.

[0003] To address the issues of multiiodine shuttle and sluggish kinetics in iodine cathodes, researchers have been continuously developing novel functionalized host materials to enhance multiiodine anchoring and reduce redox reaction barriers. Among these, covalent organic frameworks (COFs), with their designable pore structures, abundant polar sites, and good chemical stability, perfectly meet the loading and confinement requirements of iodine species and have become a new generation of high-performance iodine host materials to replace traditional carbon materials. However, the reported COF-based iodine host systems still have significant performance limitations. Their fixation of multiiodides mostly relies on weak physical / weak chemical interactions such as hydrogen bonds and van der Waals forces, resulting in limited anchoring and confinement capabilities for soluble multiiodides and an inability to completely suppress the shuttle effect. At the same time, these conventional COF materials lack precisely controllable active catalytic sites, making it difficult to regulate the redox kinetics of iodine species at the electronic structure level. This hinders the efficient reduction of multi-level reaction barriers and acceleration of interfacial charge transfer, thus making it difficult to simultaneously achieve high capacity, high rate capability, and ultra-long cycle life in zinc-iodine batteries. Against this backdrop, how to precisely design structures at the molecular scale to construct bifunctional organic framework hosts with both strong chemical anchoring capabilities and high intrinsic catalytic activity, while simultaneously solving the dual challenges of multi-iodine shuttle diffusion and reaction kinetic lag, has become a core scientific issue for breaking through the performance bottleneck of aqueous zinc-iodine batteries and promoting their large-scale energy storage applications. Summary of the Invention

[0004] To address the core technical problems of existing aqueous zinc-iodine batteries, such as polyiodide shuttle diffusion, sluggish redox reaction kinetics, high interfacial conversion energy barriers, easy loss of active materials, poor battery cycle stability, and weak host anchoring ability and lack of intrinsic catalytic activity in iodine cathodes, this invention provides a zinc-based porphyrin organic framework cathode material with bimetallic sites and its preparation method. This invention employs a stepwise condensation polymerization and subsequent precise coordination modification strategy to simultaneously construct a porphyrin-bipyridine organic framework within the porphyrin-bipyridine organic framework. Simulated active sites and The bifunctional active structure of the coordination unit overcomes the shortcomings of traditional carbon materials and single-function organic framework materials that rely solely on weak physical confinement and weak intermolecular forces to bind multiiodine species. Through a synergistic mechanism of strong chemical coordination anchoring and intrinsic electrocatalysis, it simultaneously achieves efficient immobilization of multiiodides, rapid redox conversion and stable electrode interface construction, effectively solving the technical problems of severe shuttle effect, slow reaction kinetics and rapid capacity decay over long cycles in zinc-iodine batteries.

[0005] The bimetallic site zinc-based porphyrin organic framework cathode material of this invention uses pyrrole and 5,5'-dialdehyde-2,2'-bipyridine (Bpy) as organic monomers. A highly stable and highly porous POF-Bpy organic framework precursor is constructed via a propionic acid-catalyzed dehydration condensation reaction. This framework possesses abundant bipyridine nitrogen sites and porphyrin nitrogen active sites, providing sufficient bonding sites for subsequent metal coordination modification. Further, through a post-synthetic coordination modification strategy, using anhydrous zinc halide as a modification precursor, precise coordination between zinc ions and framework nitrogen sites is achieved in a DMF solvent system. Simultaneously, halide ions are introduced to construct a local microenvironment, ultimately yielding the ZnI-POF-BpyI material. This material leverages the inherent hierarchical pore structure of POF-Bpy to achieve rapid electrolyte wetting and efficient ion transport. Simultaneously, relying on the synergistic effect of the dual zinc-coordinated active sites within the framework, it exhibits both excellent multi-iodine adsorption and anchoring performance and iodine species redox electrocatalytic activity.

[0006] The bimetallic site zinc-based porphyrin organic framework cathode material of this invention has a monodisperse, near-spherical morphology with highly uniform particle size and an average diameter of 0.8-1.2 μm. The particle surface exhibits a typical rough, porous structure, assembled from a large number of nanoparticles. XPS analysis reveals the presence of Zn 2p spectra. and Double peaks, I 3d spectrum exists and , The spectrum exists in the location and They belong to the pyrrole nitrogen in the pyrrole unit and the pyridine nitrogen in the bipyridine unit, respectively.

[0007] The bimetallic site zinc-based porphyrin organic framework cathode material of the present invention comprises the following steps: 5,5'-dialdehyde-2,2'-bipyridine and pyrrole are refluxed and stirred in propionic acid solvent; the system is cooled to a certain temperature, and the solid product is collected by centrifugation and washed successively with deionized water and ethanol; the solid is vacuum dried to finally obtain a black powder POF-Bpy, which is then uniformly dispersed with anhydrous zinc iodide in DMF and heated and stirred; the product ZnI-POF-Bpy is collected by cooling and filtration.

[0008] ZnI-POF-Bpy performance The dual-site structure with coexisting coordination units enables the framework to simultaneously possess highly efficient catalytic centers, strong adsorption sites for multiple iodides, and halogen bond donor centers. XRD confirmed a broad and distinct diffraction peak at 2θ≈22°, corresponding to the typical characteristics of amorphous conjugated polymers, indicating that the material has an amorphous structure with long-range disorder and short-range order. IR showed that the framework efficiently condenses through Schiff base reaction. XPS revealed the successful formation and coordination of Zn, which can achieve high cycle stability when applied to zinc-ion batteries.

[0009] Furthermore, in the above technical solution, the reflux heating temperature is 140-160℃ to control the degree of dehydration condensation between pyrrole and 5,5'-dialdehyde-2,2'-bipyridine (Bpy).

[0010] Furthermore, in the above technical solution, the reflux stirring time can be adjusted to 10-24 hours to adjust the size of POF particles.

[0011] Furthermore, in the above technical solution, the mass ratio of 5,5'-dialdehyde-2,2'-bipyridine to pyrrole is adjusted in the range of 1.2-2:1, preferably 1.5:1, in order to regulate the orderly and uniform growth of the precursor skeleton.

[0012] Furthermore, in the above technical solution, the vacuum drying is performed at 60 °C for 24 hours; the heating and stirring reaction in the DMF is performed at 160 °C for 6 hours.

[0013] Furthermore, in the above technical solution, the mass ratio of POF-Bpy to anhydrous zinc iodide is adjusted within the range of 1:1-2 to ensure successful coordination of Zn ions.

[0014] Further, in the above technical solution, the typical operation of this invention is as follows: 455 mg of 5,5'-dialdehyde-2,2'-bipyridine, 300 mg of pyrrole, and 30 mL of propionic acid are added sequentially to a round-bottom flask; the mixture is refluxed and stirred at 140 °C for 12 hours; after the system cools to room temperature, the solid product is collected by centrifugation, washed three times with deionized water and twice with ethanol; the washed solid is dried in a vacuum environment at 60 °C for 24 h to finally obtain a black powder POF-Bpy, which is then uniformly dispersed with anhydrous zinc iodide in 150 mL of DMF at a mass ratio of 1:1, and the mixture is stirred and reacted at 160 °C for 6 h. After cooling to room temperature, it is filtered to obtain the product ZnI-POF-Bpy.

[0015] The structural design has the following advantages: (1) The highly stable POF-Bpy porous framework provides a continuous ion / electron transport channel, and the rich hierarchical porous structure alleviates the structural deformation of iodine species during charging and discharging, providing a buffer space for electrode volume changes; (2) The framework is built-in The coordination unit can efficiently capture soluble polyiodides through strong chemical anchoring and halogen bond interaction, thereby suppressing the polyiodine shuttle effect at its source and significantly improving the stability of the electrode structure and interface; (3) High activity The coordination site can serve as an intrinsic electrocatalytic center, effectively reducing... Multi-level redox reaction energy barriers accelerate electrode reaction kinetics and realize rapid reversible conversion of iodine species; (4) The bifunctional active sites constructed by precise molecular-level coordination are uniformly distributed on the surface of the organic framework, which can effectively avoid the aggregation and deactivation of active sites, maintain the integrity of the electrode structure during long cycles, and greatly improve the rate performance and cycle stability of zinc-iodine batteries.

[0016] This invention also provides the application of the aforementioned bimetallic site zinc-based porphyrin organic framework cathode material in zinc-iodine battery cathode materials. Beneficial effects

[0017] A. The cathode material preparation process of this invention is simple, mild, and highly versatile, and can be extended to prepare various zinc halide-modified organic framework cathode materials. It provides novel design ideas and technical support for the structural design and controllable preparation of high-performance, long-life, large-scale energy storage aqueous zinc-iodine battery cathode materials, possessing extremely high engineering application value and industrialization prospects. Through a stepwise condensation polymerization and post-synthesis precise coordination modification strategy, a novel cathode material preparation process has been successfully constructed. The porphyrin-based organic framework cathode material with dual active sites effectively solves the technical drawbacks of traditional zinc-iodine batteries, such as severe iodine shuttle, slow redox kinetics, easy loss of active materials, poor electrode interface stability, and short cycle life.

[0018] B. This invention relies on the intrinsic porous framework structure of POF-Bpy to provide ample ion transport channels and electrolyte wetting space, while utilizing the functional synergistic effect of the two zinc coordination sites to achieve both... The strong chemical anchoring and halogen bond interaction of the coordination unit efficiently immobilizes soluble polyiodides, fundamentally suppressing shuttle effects and negative electrode corrosion, and also leveraging high activity The catalytic site lowers the energy barrier of multi-level redox reactions of iodine species, accelerates charge transfer and reaction kinetics, significantly improves the reversibility and structural stability of iodine cathode, and greatly enhances the rate performance and long-cycle stability of zinc-iodine batteries.

[0019] C. The technological innovation of this invention lies in the precise molecular-scale control of the coordination microenvironment of organic frameworks, achieved through a simple and controllable post-synthetic coordination process. Catalytic sites and The uniform coexistence of anchoring sites breaks through the technical bottleneck of traditional single-functional host materials that cannot simultaneously achieve multi-iodine anchoring and rapid electrocatalytic conversion. This bifunctional synergistic structure retains the advantages of porous organic frameworks, such as large specific surface area, regular pore structure, and strong structural stability, while endowing the material with excellent intrinsic catalytic activity and multi-iodine locking ability. It effectively avoids the problems of active site aggregation and deactivation and electrode structure collapse, and achieves simultaneous improvement in electrode mechanical stability, interfacial stability, and electrochemical kinetic performance.

[0020] Research has found that the bimetallic site zinc-based porphyrin organic framework cathode material ZnI-POF-Bpy described in this invention exhibits excellent electrochemical performance: exist The capacities at the given current densities were 203.3, 199.7, 187.7, 170.0, 155.9, and 144.2, respectively. Even in It maintains considerable capacity even at high rates, and It exhibits superior stability, remaining stable for 100 cycles at the specified current density. This demonstrates that the ZnI-POF-Bpy material possesses both [various properties / qualities]. Porphyrin sites and The bipyridine coordination unit is bifunctional, breaking through the limitations of traditional host-based catalytic design that relies solely on physical confinement or a single site. It provides a general molecular engineering solution for regulating the metal coordination environment and simultaneously enhancing catalysis and intermediate lock-in. This not only contributes to the development of high-performance aqueous zinc-iodine batteries, but also provides a reusable theoretical and experimental paradigm for the design of various multi-electron conversion energy storage electrodes. Attached Figure Description

[0021] Figure 1The images shown are TEM images of the ZnI-POF-Bpy material obtained in Example 1; where: (a) (b) TEM images of ZnI-POF-Bpy; (c) EDS elemental diagram of ZnI-POF-Bpy.

[0022] Figure 2 The image shows the XRD pattern of the ZnI-POF-Bpy material obtained in Example 1.

[0023] Figure 3 The image shows the IR spectrum of the ZnI-POF-Bpy material obtained in Example 1.

[0024] Figure 4 XPS spectra of the ZnI-POF-Bpy material obtained in Example 1: (a) Overall spectrum; (b) C 1s spectrum; (c) N 1s spectrum; (d) Zn 2p spectrum; (e) I 3d spectrum.

[0025] Figure 5 As obtained in Example 1 Comparison of electrochemical properties of materials; where: a) a) CV curve; b) Charge-discharge curve; c) Cyclic graph; d) Rate; e) Charge-discharge curves at different current densities; f) Self-discharge graph.

[0026] Figure 6 As obtained in Example 1 Material a) Cyclic voltammetry (CV) curves at different scan rates; b) Cyclic voltammetry (CV) curves at different scan rates The contribution percentage of electrode capacitance. Detailed Implementation Example 1

[0027] Preparation of ZnI-POF-Bpy materials

[0028] This study prepared ZnI-POF-Bpy using a modified synthetic method. First, 455 mg of 5,5'-dialdehyde-2,2'-bipyridine and 300 mg of pyrrole were added sequentially to a round-bottom flask, followed by 30 mL of propionic acid. The mixture was refluxed and stirred at 140 °C for 12 hours. After cooling to room temperature, the solid product was collected by centrifugation and washed three times with deionized water and twice with ethanol. The washed solid was then dried under vacuum at 60 °C for 24 h to obtain a black powder, POF-Bpy. The prepared POF-Bpy was then uniformly dispersed with anhydrous zinc iodide in 150 mL of DMF at a mass ratio of 1:1. The mixture was stirred and reacted at 160 °C for 6 h. After cooling to room temperature, the product ZnI-POF-Bpy was collected by filtration and washed twice each with deionized water and ethanol. The obtained solid was dried under vacuum at 60 °C overnight to obtain the target sample, designated ZnI-POF-Bpy-1.

[0029] To explore the microstructure and structural composition of the particles, the ZnI-POF-Bpy prepared above was systematically characterized by TEM. Figure 1 The ZnI-POF-Bpy material exhibits a monodisperse, near-spherical morphology with highly uniform particle size and an average diameter of approximately 1 μm. The particle surface displays a typical rough, porous structure, assembled from a large number of nanoparticles. This structure provides ample reaction sites and mass transfer channels for the adsorption of iodine species and the penetration of the electrolyte. Simultaneously, there is no significant aggregation between particles, demonstrating excellent monodispersity, which is beneficial for the uniform distribution of active materials during electrode fabrication.

[0030] XRD patterns ( Figure 2 The data shows that POF-Bpy exhibits a broad and distinct diffraction peak at 2θ≈22°, corresponding to typical characteristics of amorphous conjugated polymers, indicating that the material possesses an amorphous structure with long-range disorder and short-range order. The ZnI-POF-Bpy obtained by subsequent coordination modification showed a significant positional shift in its characteristic diffraction peaks, moving towards lower angles compared to POF-Bpy. This may be due to... With a large ionic radius, it generates a stronger steric hindrance effect when coordinating with bipyridine sites and embedding into the framework, causing more significant expansion and stretching of the layered or chain-like framework. This halogen-regulated framework expansion and pore widening not only provide more space for iodine loading and polyiodide confinement, but also increase the exposure of active sites and enhance ion transport capabilities, providing a key structural basis for achieving efficient electron conversion, excellent rate performance, and ultra-long cycling stability.

[0031] IR curve ( Figure 3 The results showed that the characteristic absorption peaks of the aldehyde and amino groups in the monomers were significantly weakened or even disappeared, while at the same time... The presence of a distinct C=N stretching vibration peak confirms that the framework undergoes efficient condensation via a Schiff base reaction. The observation of characteristic vibrational signals of Zn–N in the vicinity directly proves that the Zn ion has successfully coordinated with the nitrogen ligand.

[0032] Figure 4 XPS analysis revealed the surface chemical information of the material: the high-resolution Zn 2p spectrum of ZnI-POF-Bpy showed two characteristic peaks at binding energies of 1021.9 eV and 1045.1 eV, respectively, corresponding to... Spin-orbit splitting peaks. The peak positions of the two characteristic peaks and the approximately 23.2 eV spin-orbit splitting distance confirm that zinc exists in the material in the +2 oxidation state, proving that zinc ions successfully coordinate with the organic framework, achieving effective loading of zinc active sites. The high-resolution spectrum of pure POF-Bpy N1s can be fitted with two characteristic peaks, with binding energies at 400.2 eV and 399.1 eV, which are attributed to pyrrole nitrogen in the pyrrole unit and pyridine nitrogen in the bipyridine unit, respectively. After zinc ion coordination modification, a new Zn–N bond characteristic peak appears at 398.6 eV in the ZnI-POF-Bpy N1s spectrum, while the original nitrogen characteristic peak undergoes a positive shift of approximately 0.50 eV. These results indicate that nitrogen atoms in the framework undergo electronic delocalization to zinc ions, achieving uniform surface charge distribution of nitrogen atoms, further verifying... It successfully coordinated with the nitrogen site in the framework.

[0033] In the ZnI-POF-Bpy I 3d high-resolution XPS spectrum, two typical characteristic peaks were observed at 619.0 eV and 630.5 eV, respectively, corresponding to... The characteristic peak of spin-orbit splitting. This result directly confirms the presence of iodide ions. It was successfully introduced into the organic framework as a coordinating anion and maintained a stable chemical state in the framework coordination structure. Example 2

[0034] This study prepared ZnI-POF-Bpy using a modified synthesis scheme. First, 455 mg of bipyridine dialdehyde (Bpy) and 300 mg of pyrrole were added sequentially to a round-bottom flask, followed by 30 mL of propionic acid. The mixture was refluxed at 150 °C and stirred for 12 hours. After cooling to room temperature, the solid product was collected by centrifugation and washed three times with deionized water and twice with ethanol. The washed solid was then dried under vacuum at 60 °C for 24 h to obtain a black powdery POF-Bpy. The prepared POF-Bpy was then uniformly dispersed with anhydrous zinc iodide at a mass ratio of 1:1 in 150 mL of DMF, and the mixture was stirred at 160 °C for 6 h. After cooling to room temperature, the product ZnI-POF-Bpy was collected by filtration and washed twice each with deionized water and ethanol. The obtained solid was dried under vacuum at 60 °C overnight to obtain the target sample, designated ZnI-POF-Bpy-2. Example 3

[0035] This study prepared ZnI-POF-Bpy using a modified synthetic method. First, 455 mg of 5,5'-dialdehyde-2,2'-bipyridine and 300 mg of pyrrole were added sequentially to a round-bottom flask, followed by 30 mL of propionic acid. The mixture was refluxed at 150 °C and stirred for 16 hours. After cooling to room temperature, the solid product was collected by centrifugation and washed three times with deionized water and twice with ethanol. The washed solid was then dried under vacuum at 60 °C for 24 h to obtain a black powder, POF-Bpy. The prepared POF-Bpy was then uniformly dispersed with anhydrous zinc iodide in 150 mL of DMF at a mass ratio of 1:1. The mixture was stirred at 160 °C for 6 h. After cooling to room temperature, the product ZnI-POF-Bpy was collected by filtration and washed twice each with deionized water and ethanol. The obtained solid was dried under vacuum at 60 °C overnight to obtain the target sample, designated ZnI-POF-Bpy-3. Example 4

[0036] This study prepared ZnI-POF-Bpy using a modified synthetic method. First, 455 mg of 5,5'-dialdehyde-2,2'-bipyridine and 300 mg of pyrrole were added sequentially to a round-bottom flask, followed by 30 mL of propionic acid. The mixture was refluxed at 150 °C with stirring for 24 hours. After cooling to room temperature, the solid product was collected by centrifugation and washed three times with deionized water and twice with ethanol. The washed solid was then dried under vacuum at 60 °C for 24 h to obtain a black powder, POF-Bpy. The prepared POF-Bpy was then uniformly dispersed with anhydrous zinc iodide at a mass ratio of 1:1 in 150 mL of DMF, and the mixture was stirred at 160 °C for 6 h. After cooling to room temperature, the product ZnI-POF-Bpy was collected by filtration and washed twice each with deionized water and ethanol. The obtained solid was dried under vacuum at 60 °C overnight to obtain the target sample, designated ZnI-POF-Bpy-4. Example 5

[0037] This study prepared ZnI-POF-Bpy using a modified synthetic method. First, 455 mg of 5,5'-dialdehyde-2,2'-bipyridine and 300 mg of pyrrole were added sequentially to a round-bottom flask, followed by 30 mL of propionic acid. The mixture was refluxed at 150 °C with stirring for 24 hours. After cooling to room temperature, the solid product was collected by centrifugation and washed three times with deionized water and twice with ethanol. The washed solid was then dried under vacuum at 60 °C for 24 h to obtain a black powder, POF-Bpy. The prepared POF-Bpy was then uniformly dispersed with anhydrous zinc iodide at a mass ratio of 1:2 in 150 mL of DMF, and the mixture was stirred at 160 °C for 6 h. After cooling to room temperature, the product ZnI-POF-Bpy was collected by filtration and washed twice each with deionized water and ethanol. The obtained solid was dried under vacuum at 60 °C overnight to obtain the target sample, which is denoted as ZnI-POF-Bpy-5. Example 6

[0038] This study prepared ZnI-POF-Bpy using a modified synthetic method. First, 455 mg of 5,5'-dialdehyde-2,2'-bipyridine and 300 mg of pyrrole were added sequentially to a round-bottom flask, followed by 30 mL of propionic acid. The mixture was refluxed at 150 °C and stirred for 24 hours. After cooling to room temperature, the solid product was collected by centrifugation and washed three times with deionized water and twice with ethanol. The washed solid was then dried under vacuum at 60 °C for 24 h to obtain a black powder, POF-Bpy. The prepared POF-Bpy was then uniformly dispersed with anhydrous zinc iodide at a mass ratio of 1:2 in 150 mL of DMF, and the mixture was stirred at 160 °C for 8 h. After cooling to room temperature, the product ZnI-POF-Bpy was collected by filtration and washed twice each with deionized water and ethanol. The obtained solid was dried under vacuum at 60 °C overnight to obtain the target sample, which is denoted as ZnI-POF-Bpy-6. Example 7

[0039] This study prepared ZnI-POF-Bpy using a modified synthetic method. First, 455 mg of 5,5'-dialdehyde-2,2'-bipyridine and 300 mg of pyrrole were added sequentially to a round-bottom flask, followed by 30 mL of propionic acid. The mixture was refluxed at 150 °C and stirred for 24 hours. After cooling to room temperature, the solid product was collected by centrifugation and washed three times with deionized water and twice with ethanol. The washed solid was then dried under vacuum at 60 °C for 24 h to obtain a black powder, POF-Bpy. The prepared POF-Bpy was then uniformly dispersed with anhydrous zinc iodide at a mass ratio of 1:2 in 150 mL of DMF, and the mixture was stirred at 160 °C for 10 h. After cooling to room temperature, the product ZnI-POF-Bpy was collected by filtration and washed twice each with deionized water and ethanol. The obtained solid was dried under vacuum at 60 °C overnight to obtain the target sample, designated ZnI-POF-Bpy-7. Example 8

[0040] Electrochemical applications of ZnI-POF-Bpy To investigate the adsorption and transformation behavior of iodine in covalent organic framework materials, A CR2032 coin cell was assembled using zinc foil as the electrolyte, zinc sheet as the negative electrode, and titanium foil as the current collector. The system was then evaluated. and Positive electrode electrochemical performance. The cyclic voltammetry (CV) curves measured at the scan rate showed obvious redox peaks, corresponding to the continuous reduction and oxidation process of iodine species. It exhibits a stronger current response and a smaller redox potential difference, far superior to This demonstrates that the introduction of dual-site synergy and halogen bond anchoring significantly reduces electrode polarization and accelerates iodine redox kinetics. Figure 5 a).

[0041] The constant current charge-discharge curve shows that Release based on iodine quality High specific capacity ( Figure 5 b), significantly higher than This directly confirms the positive effect of dual-site synergy and halogen bond anchoring on capacity enhancement. The capacity retention rate remains as high as 95.3% at various rate ratios. Figure 5 c) Rate performance tests show that... The capacities at current densities of 0.4, 0.5, 1, 2, 3, 4, and 5 A g⁻¹ are 203.3, 199.7, 187.7, 170.0, 155.9, and 144.2, respectively. ( Figure 5 (d, e) Self-discharge tests showed that after standing for 24 hours... The open-circuit voltage stabilizes at 1.35 V. Figure 5 f).

[0042] To reveal the mechanism by which bimetallic site synergy and halogen bond anchoring regulate charge storage dynamics, in Within the scan speed range, the system compared... and Cyclic voltammetric behavior at the positive electrode. The redox peak current and scan rate were fitted using the power function formula i=aνb to calculate the kinetic value of b. Typically, the b value is between 0.5 and 1; a value close to 0.5 indicates that the process is controlled by ion diffusion, while a value close to 1 indicates that capacitance control is dominant. The fitting results show that... The two sets of redox peaks corresponded to b-values ​​of 0.75 and 0.84, respectively, both significantly higher than [the values ​​indicated by the previous data]. This indicates that the synergistic effect of the two sites effectively increased the proportion of capacitive contribution. Quantitative analysis of capacitive contribution shows that... Capacitor contribution rate from The percentage increased to 62%. 78% at the time Figure 6 (a, b) The above results fully demonstrate that charge storage in ZnI-POF-Bpy is mainly characterized by surface-controlled capacitive behavior, an advantage attributed to the coordination iodine pairs. The synergistic effect of electronic regulation at the site and halogen bond anchoring accelerating interfacial charge transfer together achieves efficient and rapid energy storage.

[0043] In summary, addressing the key bottlenecks commonly found in aqueous zinc-iodine batteries, such as severe multiiodide shuttle, sluggish iodine redox kinetics, and poor reversibility of high-valent iodine species, a post-synthetic coordination modification strategy was employed to precisely construct a system that combines these characteristics. Porphyrin sites and A bifunctional ZnI-POF-Bpy cathode material with bipyridine coordination units. Utilizing the synergistic effect of bimetallic sites and the halogen bond anchoring mechanism induced by coordinated iodine, an integrated synergistic optimization of electronic structure regulation and in-situ confinement by polyiodides was successfully achieved. Therefore, The cathode exhibits excellent electrochemical performance. The cathode achieved a high specific capacity of 210.5 mAh / g in 2 mol / L zinc sulfate electrolyte and at a current density of 0.3 A / g. These results fully demonstrate that this study breaks through the design limitations of traditional host catalysis that relies solely on physical confinement or single-site catalysis, and provides a general molecular engineering scheme for regulating the metal coordination environment and simultaneously enhancing catalysis and intermediate lock-in. This not only contributes to the development of high-performance aqueous zinc-iodine batteries, but also provides a reusable theoretical and experimental paradigm for the design of various multi-electron conversion energy storage electrodes.

Claims

1. A zinc-based porphyrin organic framework cathode material with bimetallic sites, characterized in that: The cathode material exhibits a monodisperse, near-spherical morphology with highly uniform particle size and an average diameter of 0.8-1.2 μm. The particle surface displays a typical rough, porous structure, assembled from a large number of nanoparticles. In XPS, the Zn 2p spectrum shows double peaks at 1021.9 eV and 1045.1 eV, the I 3d spectrum shows peaks at 619.0 eV and 630.5 eV, and the N 1s spectrum shows peaks at 400.2 eV and 399.1 eV, which are attributed to pyrrole nitrogen in the pyrrole unit and pyridine nitrogen in the bipyridine unit, respectively.

2. The method for preparing the bimetallic site zinc-based porphyrin organic framework cathode material as described in claim 1, characterized in that, The process includes the following steps: 5,5'-dialdehyde-2,2'-bipyridine and pyrrole are refluxed and stirred in propionic acid solvent; the system is cooled to a certain temperature, and the solid product is collected by centrifugation and washed successively with deionized water and ethanol; the solid is dried under vacuum to obtain a black powder POF-Bpy, which is then uniformly dispersed with anhydrous zinc iodide in DMF and heated and stirred; the product ZnI-POF-Bpy is collected by cooling and filtration.

3. The method for preparing the bimetallic site zinc-based porphyrin organic framework cathode material according to claim 2, characterized in that: The reflux heating temperature is 140-160℃, which promotes the dehydration condensation reaction between pyrrole and 5,5'-dialdehyde-2,2'-bipyridine to construct a regular porphyrin-based organic framework; the stirring reaction time is 10-24 hours to adjust the size of POF particles.

4. The method for preparing the bimetallic site zinc-based porphyrin organic framework cathode material according to claim 2, characterized in that: The mass ratio of 5,5'-dialdehyde-2,2'-bipyridine to pyrrole is 1.2-2:1 to regulate the orderly and uniform growth of the precursor skeleton; the mass ratio of POF-Bpy to anhydrous zinc iodide is 1:1-2 to ensure successful coordination of Zn ions.

5. The method for preparing the bimetallic site zinc-based porphyrin organic framework cathode material according to claim 2, characterized in that: Vacuum drying was carried out at 60 °C for 24 hours; the reaction in DMF was carried out at 160 °C with stirring for 6 hours.

6. The method for preparing the bimetallic site zinc-based porphyrin organic framework cathode material according to any one of claims 2-5, characterized in that, A typical preparation procedure is as follows: 455 mg of 5,5'-dialdehyde-2,2'-bipyridine, 300 mg of pyrrole, and 30 mL of propionic acid are added sequentially to a round-bottom flask; the mixture is refluxed and stirred at 140 °C for 12 hours; after the system cools to room temperature, the solid product is collected by centrifugation and washed three times with deionized water and twice with ethanol; the washed solid is dried under vacuum at 60 °C for 24 h to obtain a black powder POF-Bpy, which is then uniformly dispersed with anhydrous zinc iodide in 150 mL of DMF at a mass ratio of 1:1, and the mixture is stirred at 160 °C for 6 h. After cooling to room temperature, the mixture is filtered to obtain the product ZnI-POF-Bpy.

7. The application of the bimetallic site zinc-based porphyrin organic framework cathode material as described in claim 1 in zinc-iodine battery cathode materials.